Developing English Material Through Picture Slide for Teaching Writing of Vocational School - Tety Mariana (Journal of English Language Teaching and Islamic Integration, 2018)
The purpose of developing English material through  picture slide is to develop English material in the form of pictures slide show in order to improve the competence of students in writing descriptive text for  ten  graders  of  Vocational  High  School.  The  development  of  this learning material is based on Borg and Gall's Research Development (R &  D)  concept  theory  by  following  steps  design  of  needs  analysis, material  development,  expert  validation,  pilot  and  final  product.  The result of the development of this product is a picture slide material. It can  be  used  and  developed  as  a  medium  of  teaching  English  for students in order to improve their writing skill and increase the student's motivation  to  learn.  The  development  of  teaching  material  is  able  to provide different way in English learning especially in teaching English of  writing  descriptive  text.  Students  have  motivation  in  learning descriptive text in this case is to write a text. Teaching material through picture slide can be developed again in accordance  with the needs of students by practitioners and English teachers.